Who benefits from the decentralized energy system (DES)? Evidence from Nepal's micro-hydropower (MHP) - Mukti Nath Subedi; Bishal Bharadwaj; Shuddhasattwa Rafiq (ZBW - Leibniz Information Centre for Economics, 2021)
– In low-income countries, uneven access to clean energy has posed a challenge to reduce socioeconomic inequalities across gender and disadvantaged groups. To address this issue, development planners see potentials from the decentralized energy system (DES) that provides electricity access in those areas where the national electricity grid is not available. To assess whether the DES helps reduce inequality and improve gender empowerment, this study focuses on the micro-hydropower (MHP) scheme, a widely adopted DES in Nepal, to study its impact on educational attainment and employment outcomes by caste and gender. The results show MHP improves the educational outcomes and facilitates a labour shift from traditional agriculture to waged and salaried jobs. However, a disaggregated analysis shows the educational outcome of access to MHP electricity is higher for women and lower caste individuals; however, the positive employment related effects are inclined toward socially dominant groups like males and upper caste individuals. These results reveal that while in general the DES improves educational and labour market outcomes, it may need complementary conditions to signify its labour effects on women and lower caste individuals.
Keywords: I25; J15; Q42; 330; Decentralized energy system; education; labour market; caste; gender